How do you find the sum of Sigma (3i-1) from i=1 to 6? Calculus Introduction to Integration Sigma Notation 1 Answer Pankaj Solanki Sep 22, 2017 57 Explanation: Sigma_1^6(3i-1) -1 is repeated 6 times Sigma_1^6(3i)-6 =3(1+2+3+4+5+6)-6 =3(21)-6 =63-6=57 Answer link Related questions How does sigma notation work? How do you use sigma notation to represent the series 1/2+1/4+1/8+…? Use summation notation to express the sum? What is sigma notation for an arithmetic series with first term a and common difference d ? How do you evaluate the sum represented by sum_(n=1)^5n/(2n+1) ? How do you evaluate the sum represented by sum_(n=1)^(8)1/(n+1) ? How do you evaluate the sum represented by sum_(n=1)^(10)n^2 ? What is sigma notation for a geometric series with first term a and common ratio r ? What is the value of 1/n sum_{k=1}^n e^{k/n} ? Question #07873 See all questions in Sigma Notation Impact of this question 6333 views around the world You can reuse this answer Creative Commons License